2022
DOI: 10.3390/jcm11175134
|View full text |Cite
|
Sign up to set email alerts
|

Potential Risk of Overtreatment in Patients with Type 2 Diabetes Aged 75 Years or Older: Data from a Population Database in Catalonia, Spain

Abstract: Aim: To assess the potential risk of overtreatment in patients with type 2 diabetes (T2DM) aged 75 years or older in primary care. Methods: Electronic health records retrieved from the SIDIAP database (Catalonia, Spain) in 2016. Variables: age, gender, body mass index, registered hypoglycemia, last HbA1c and glomerular filtration rates, and prescriptions for antidiabetic drugs. Potential overtreatment was defined as having HbA1c < 7% or HbA1c < 6.5% in older patients treated with insulin, sulfonylureas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 38 publications
1
8
0
1
Order By: Relevance
“…The level of overtreatment of T2DM in our study is comparable to recent studies also having documented a higher proportion of overtreatment than undertreatment 7,9,10,15,16 . A US study using Medicare data found that 11% of patients 65 years and older with T2DM were overtreated, and deintensification of overtreatment by reducing therapy took place only in about 14% 10,17 .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The level of overtreatment of T2DM in our study is comparable to recent studies also having documented a higher proportion of overtreatment than undertreatment 7,9,10,15,16 . A US study using Medicare data found that 11% of patients 65 years and older with T2DM were overtreated, and deintensification of overtreatment by reducing therapy took place only in about 14% 10,17 .…”
Section: Discussionsupporting
confidence: 87%
“…A strength of the present study is the focus on multimorbid older patients with polypharmacy, a population commonly excluded from trials, including large studies on T2DM, 2,19 but evaluated in larger observational studies in this context before 7–9 . In addition, the inclusion of OPERAM patients allowed consideration of multiple relevant covariates in the treatment of T2DM, including patient‐relevant outcomes 11,20 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations